An Assessment of Gender Inequality: A Case Study of Pakistan - Azeema Begam; Nooreen Mujahid (International Journal on Women Empowerment, 2019)
Background: The gender assessment highlights the prevailing gap in multiple dimensions that exist between males and females, and challenges which Pakistan faces related to gender issues. Achieving this objective requires in-depth understanding of economic and non-economic factors because the existing data only provide gender differences in selected dimensions such as, education, health, political and labour force participation. Moreover, gender gap is observable due to lack of access to resources and opportunities, constrains on female’s mobility, lack of education and information. Methodology: The study presents a detailed gender assessment to explore gender gap in political participation, health, education and economic activity in Pakistan. The analysis is based on the secondary data drawn from reports published by several governmental, international development agencies, and local non-governmental organizations. The gender disparity between male and female’s living create biasness which leads to social, cultural and economic inequality. Therefore, this assessment enlightens gender roles, relations and control over resources between both genders in order to realize full potential and constrains of economic and human development. Results: Findings from gender assessment can be used to formulate various strategies and policies for addressing gender issues. Conclusion: Public policies related to government spending on health and education should be targeted on the basis of gender while identify the regions where higher gender disparity exists. Especially government spending on education and health will play significant role in betterment of females in rural areas.